Trialectic of a sports space: strong girls - Cortés Romero, Edith; Valenzuela Ornelas, Elizabeth (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The purpose of the following proposal is to present the Strong Girls program that seeks to publicize the participation of women in sports, as well as to show the barriers and challenges they face in women's sports. For which the theoretical approach is based on the trialectic of Edward Soja, when investigating space, time and society in relation to the participation of women in sport, and how Strong Girls uses streaming as a means to promote gender equality and increase the visibility of female athletes. For the methodology, Strong Girls was used as a case study, and a combination of qualitative and quantitative methods was used to collect data from the programs and analyze the sports diffusion, taking up experiences of individual and team sports. The findings of the project is the identification of the barriers that women face, such as gender stereotypes, lack of opportunities and discrimination, as well as Strong Girls is an inclusive space, supportive by promoting networks and sharing experiences among athletes to overcome obstacles. Likewise, as the program for three years has been able to show the role of women athletes, promoting the visibility of the sports they practice and promoting knowledge of everything that sports entails. Keywords: women's sport, space, streaming, diffusion